Purinoceptor P2K1/DORN1 Enhances Plant Resistance Against a Soilborne Fungal Pathogen, Rhizoctonia solani - Kumar, Sonika; Tripathi, Diwaker; Okubara, Patricia A.; Tanaka, Kiwamu (Frontiers in Plant Science, 2020)
The purinoceptor P2K1/DORN1 recognizes extracellular ATP, a damage-associated molecular pattern (DAMP) released upon cellular disruption by wounding and necrosis, which in turn, boost plant innate immunity. P2K1 is known to confer plant resistance to foliar biotrophic, hemi-biotrophic, and necrotrophic pathogens. However, until now, no information was available on its activity against root pathogens. In this report, we describe the contribution of P2K1 to resistance in Arabidopsis against Rhizoctonia solani, a broad host range, necrotrophic soilborne fungal pathogen. In pot assays, the Arabidopsis P2K1 overexpression line OxP2K1 showed longer root length and a greater rosette surface area than wild type in the presence of the pathogen. In contrast, the knockout mutant dorn1-3 and the double mutant rbohd/f, defective in two subunits of the respiratory burst complex NADPH oxidase, exhibited significant reductions in shoot and root lengths and rosette surface area compared to wild type when the pathogen was present. Root expression of PR1, PDF1.2 and JAZ5 was reduced in dorn1-3 and rbohd/f and elevated in OxP2K1 relative to wild type, indicating that the salicylate and jasmonate defense signaling pathways functioned in resistance. These results indicated that a DAMP-mediated defense system confers basal resistance against an important root necrotrophic fungal pathogen.